Desain Pembelajaran Mendalam untuk Meningkatkan Keterampilan Berbicara pada Pembelajaran Bahasa Arab: Immersive Learning Design to Improve Speaking Skills in Arabic Language Learning - Vero Ananda Putra; Chakam Failasuf; Ihwan Rahman Bahtiar; Romdani Romdani (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
Arabic language learning at the senior secondary level is still dominated by a theoretical linguistic approach that focuses on mastery of grammar, thus providing little space for the development of speaking skills (maharah kalam). This condition has implications for low active participation of students, increased language anxiety, and the formation of a static mindset that inhibits the courage to communicate verbally. This study aims to develop an Arabic language learning design based on the principles of Deep Learning to improve the speaking skills of class XII Religious students at MAS PERSIS 69 Jakarta. The method used is Research and Development (R&D) with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The product developed is a comprehensive learning device that includes the Annual Program, Semester Program, and Lesson Implementation Plan (RPP), based on Project-Based Learning, and integrates the principles of Consciousness, Meaningfulness, and Joy. The validation results show that the device obtained very good scores from material experts (3.7) and Deep Learning experts (3.8). Implementation on 15 students showed significant improvement in speaking skills, marked by an increase in average scores from 77 in the pre-test to 86 in the post-test, as well as an increase in active participation from 13% to 53%. These findings indicate that the immersive learning design is not only effective in improving students' linguistic performance but also in reducing affective barriers and creating a safe, proactive, and meaningful learning environment. Therefore, the developed learning tool is deemed feasible and relevant for implementation in Arabic language learning at Madrasah Aliyah (Islamic Senior High School).